+0  
 
0
272
2
avatar+233 

What is (f−g)(x)?

 Jan 31, 2019

Best Answer 

 #1
avatar+7825 
+3

\(f(x) = 3x^5 + 6x^2 - 5\\ g(x) = 2x^4+7x^2-x+16\\ (f-g)(x) = (3x^5+6x^2-5)-(2x^4+7x^2-x+16)\\ (f-g)(x) = (3x^5+6x^2-5)-2x^4-7x^2+x-16\\ (f-g)(x) = 3x^5-2x^4-x^2+x-21\)

.
 Feb 1, 2019
 #1
avatar+7825 
+3
Best Answer

\(f(x) = 3x^5 + 6x^2 - 5\\ g(x) = 2x^4+7x^2-x+16\\ (f-g)(x) = (3x^5+6x^2-5)-(2x^4+7x^2-x+16)\\ (f-g)(x) = (3x^5+6x^2-5)-2x^4-7x^2+x-16\\ (f-g)(x) = 3x^5-2x^4-x^2+x-21\)

MaxWong Feb 1, 2019
 #2
avatar+233 
+1

thank you

skye25  Feb 5, 2019

16 Online Users

avatar
avatar
avatar